Gambling in the Bophuthatswana Sun: Sun City and the political economy of a Bantustan casino:1965-1994 - Van der Merwe, Nicola Sarah (My University, 2017)
This thesis examines the role of the Sun City casino within the context of apartheid homeland policy. The casino was established in the bantustan of Bophuthatswana in 1979, following the abolition of gambling in South Africa, with introduction of the 1965 Gambling Act. This study is motivated by two research questions: (1) the political and economic effects of the casino’s operation in Bophuthatswana; and (2) Sun City’s promotion of Bophuthatswana’s status as an independent state from South Africa. The research for this project was obtained through archival and manuscript materials, oral interviews as well as newspapers archives. The thesis is divided into five chapters which track the trajectory of Sun City’s development. The development and construction of Sun City are explored with regards to the financial contributions by the Bophuthatswana and South African governments. Secondly, the role that the governments of Bophuthatswana and South Africa played in the development of the casino and the political impact thereof. Further, the employment at the casino is investigated, regarding the economic promises made to the both the governments by Southern Sun. The area surrounding Sun City had a high unemployment rate and the resort was promoted as means to curtail this problem. The attractions Sun City offered such as burlesque shows and prostitution are discussed, with specific reference to the casino as a place of racial integration and conspicuous consumption. The sanctions and boycotts are explored regarding the cohort of international sporting and musical entertainers hosted at Sun City and the shifts in the boycott following 1990. Lastly, the fall of bantustan policy is outlined, for the reincorporation of bantustan territories into South Africa highlighted questions of gambling legality. This thesis concludes that Sun City brought exposure and infrastructure to Bophuthatswana, but most of the motivations employed to build the casino, such as high taxation, increased employment and the development of a heritage for the ‘Tswana’ people never materialised. The Sun City casino scheme aimed to further enrich individuals such as Kerzner and Mangope and the marketed benefits were not realised for the Bophuthatswana citizens.
Thesis presented in fulfilment of requirements for the degree of MA at the University of the Witwatersrand, 2017
Keywords: Bophuthatswana (South Africa)--Politics and government; Bophuthatswana (South Africa)--Economic conditions; Homelands (South Africa); Gambling--Government policy--South Africa; Casinos--Government--South Africa; Sun City (South Africa)